Hierarchically porous few-layer porphyrinic carbon nanosheets formed by a VOx-templating method for high-efficiency oxygen electroreduction. Issue 19 (22nd April 2016) - Kong, A.; Mao, C.; Wang, Y.; Lin, Q.; Bu, X.; Feng, P.
Abstract : Few-layer porous porphyrinic carbon nanosheets with highly efficient oxygen electroreduction performance were obtained by thermal conversion of Fe-porphyrin/V2 O5 intercalation compounds. Abstract : A new vanadium oxide-templating synthesis strategy is used to synthesize porous few-layer porphyrinic carbon nanosheets (PPCNs) with highly efficient electrocatalytic activity for oxygen reduction reaction (ORR). Fe-porphyrin precursors were intercalated into V2 O5 layers and directly transformed to carbon nanosheets after pyrolysis. Highly accessible porphyrinic Fe–N4 moieties embedded within few-layer carbon nanosheets with hierarchical porosity and high surface area (1600 m 2 g −1 ) were obtained. The PPCNs were demonstrated as excellent non-precious metal catalysts for ORR in both alkaline and acidic media. Specifically, the PPCNs exhibited a more positive half-wave potential than commercial Pt/C (20 wt%) in an alkaline medium at a lower catalyst loading. Moreover through further pyrolysis treatment, the catalytic activity and durability of PPCNs for ORR in both media could be further improved. The novel synthesis method presented here opens up a new route to creating novel carbon nanomaterials for various applications.